Physiological drift during steady-state exercise based on the incremental Talk Test - Foster, Carl; Walraven, Lee; Bok, Daniel; Barroso, Renato; Boullosa, Daniel; Casado, Arturo; Cortis, Cristina; De Koning, Jos J.; Festino, Emanuel; Fusco, Andrea; Rodriguez-Marroyo, Jose; Porcari, John P. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. The Talk Test (TT) is recognised as a practical method for prescribing exercise intensity during incremental exer-cise, although its applicability to prolonged steady-state exercise – particularly with respect to physiological drift – remains underexplored. Therefore, this study aimed to evaluate whether workloads at different TT stages during incremental exercise predict responses during steady-state training.Methods. Well-trained individuals (1–3 h of hiking, 3–4 times per week) performed incremental exercise (2-min stages) to determine the equivocal (EQ), last positive (LP) and last positive-1 (LP-1) TT stages. Participants then completed 60-min uphill walking bouts at LP-1, LP and EQ intensities in random order. Repeated measures ANOVA with Tukey post-hoc tests assessed differences in physiological drift across TT stages during steady-state exercise.Results. During LP-1 and LP bouts, stable conditions were observed for the percentage of maximum heart rate (% HRmax) (< 85% HRmax), rating of perceived exertion (RPE) (< 4/10), blood lactate (2–3 mmol · l–1) and TT score (~1.2/3). In contrast, during EQ, all values showed significant drift, including HR (> 95% HRmax), RPE (~7/10), blood lactate (~7 mmol · l–1) and TT score (~2.4/3).Conclusions. Training intensity based on LP-1 or LP incremental TT provides conditions consistent with the moderate-inten-sity domain, with minimal drift during 60-min exercise. Steady-state exercise at the intensity of the EQ stage results in significant drift, comparable with the heavy or severe exercise domain (> maximal lactate steady-state). These findings suggest that TT-based intensities, particularly LP-1, may be suitable for prolonged training in physically active individuals, to build endurance. Future research should investigate the applicability of the TT in athletes, particularly its effectiveness for prolonged exercise.
Keywords: exercise prescription; Talk Test; heart rate; blood lactate; rating of perceived exertion